The Use of Music in the Treatment and Management of Serious Mental Illness: A Global Scoping Review of the Literature - Golden, Tasha L.; Springs, Stacey; Kimmel, Hannah J.; Gupta, Sonakshi; Tiedemann, Alyssa; Sandu, Clara C.; Magsamen, Susan (Frontiers in Psychology, 2021)
Mental and substance use disorders have been identified as the leading cause of global disability, and the global burden of mental illness is concentrated among those experiencing disability due to serious mental illness (SMI). Music has been studied as a support for SMIs for decades, with promising results; however, a lack of synthesized evidence has precluded increased uptake of and access to music-based approaches. The purpose of this scoping review was to identify the types and quantity of research at intersections of music and SMIs, document evidentiary gaps and opportunities, and generate recommendations for improving research and practice. Studies were included if they reported on music's utilization in treating or mitigating symptoms related to five SMIs: schizophrenia, bipolar disorder, generalized anxiety disorder, major depressive disorder, or post-traumatic stress disorder. Eight databases were searched; screening resulted in 349 included studies for data extraction. Schizophrenia was the most studied SMI, with bipolar disorder studied the least. Demographics, settings, and activity details were found to be inconsistently and insufficiently reported; however, listening to recorded music emerged as the most common musical activity, and activity details appeared to have been affected by the conditions under study. RCTs were the predominant study design, and 271 unique measures were utilized across 289 primary studies. Over two-thirds of primary studies (68.5%) reported positive results, with 2.8% reporting worse results than the comparator, and 12% producing indeterminate results. A key finding is that evidence synthesis is precluded by insufficient reporting, widely varied outcomes and measures, and intervention complexity; as a result, widespread changes are necessary to reduce heterogeneity (as feasible), increase replicability and transferability, and improve understandings of mechanisms and causal pathways. To that end, five detailed recommendations are offered to support the sharing and development of information across disciplines.